2019
DOI: 10.1002/mdc3.12730
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐state Functional MRI in Parkinsonian Syndromes

Abstract: Background Background: Functional MRI (fMRI) has been widely used to study abnormal patterns of functional connectivity at rest in patients with movement disorders such as idiopathic Parkinson's disease (PD) and atypical parkinsonisms. Methods Methods: This manuscript provides an educational review of the current use of resting-state fMRI in the field of parkinsonian syndromes. ResultsResults: Resting-state fMRI studies have improved the current knowledge about the mechanisms underlying motor and non-motor sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 116 publications
(197 reference statements)
4
28
0
Order By: Relevance
“…As it is clear from Additional file 1 the findings are scattered and show very little overlap (Additional file 1). Moreover, none of the reported FC changes may be specific for migraine as other studies reported similar or exact same network changes in several other conditions, including fibromyalgia [33], Parkinsonian syndromes [34, 35] altered consciousness states [36], systemic lupus [37] and chronic hepatitis C virus infection [38]. Thus, it can be suspected that this FC method is at all not reproducible, which may be due to lack of sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 97%
“…As it is clear from Additional file 1 the findings are scattered and show very little overlap (Additional file 1). Moreover, none of the reported FC changes may be specific for migraine as other studies reported similar or exact same network changes in several other conditions, including fibromyalgia [33], Parkinsonian syndromes [34, 35] altered consciousness states [36], systemic lupus [37] and chronic hepatitis C virus infection [38]. Thus, it can be suspected that this FC method is at all not reproducible, which may be due to lack of sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 97%
“…Parkinson’s disease (PD) is the second most common neurodegenerative disorder and is characterized by dopamine depletion in the nigro-striatal system leading to progressive functional impairment (Poewe et al, 2017). Widespread functional rearrangements related to the development of motor and non-motor symptoms occur over the clinical progression in PD patients (Filippi et al, 2019). Several RS fMRI studies have identified alterations of the cerebello-thalamo-cortical circuit as a key hallmark of PD (Helmich et al, 2010; Hacker et al, 2012; Agosta et al, 2014; Akram et al, 2017), with reduced activation of the posterior putamen correlating with motor impairment as the most consistent finding (Herz et al, 2014).…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Functional connectivity (FC) quantifies the temporal correlation of functional activation in different brain regions and can be expressed in terms of pairwise Pearson’s correlation coefficients, covariance, or mutual information between time series, revealing specific networks (Smitha et al, 2017). FC has been recognized as an important biomarker for better understanding the pathophysiological mechanisms of numerous neurodegenerative diseases, including Alzheimer’s disease (AD) (Filippi et al, 2017), Parkinson’s disease (PD) (Baggio et al, 2015; Filippi et al, 2019), and frontotemporal dementia (FTD) (Filippi et al, 2017).…”
Section: Introduction: From Static To Dynamic Functional Connectivitymentioning
confidence: 99%
“…Higher co-activation at rest among regions is interpreted as a measure of higher intrinsic connectivity or cohesiveness between those regions. Initial evidence suggests that higher connectivity between basal ganglia and other regions predicts better motor performance in patients with Parkinsonian Syndromes ( Filippi et al, 2019 ) and in healthy adults ( Boyne et al, 2018 , Zwergal et al, 2012 ). However, prior studies have not accounted for the contribution of impairment of other age-related factors influencing locomotion including muscle strength ( McLean et al, 2014 ), vision ( Chaudhry et al, 2010 ), joint pain ( White et al, 2013 ), and obesity ( Vincent et al, 2010 ) as well as WMH and brain volume ( Rosso et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%